2022
DOI: 10.1038/s41398-022-02067-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary fat consumption on Alzheimer’s disease pathogenesis in mouse models

Abstract: Alzheimer’s disease (AD) is a fatal cognitive disorder with proteinaceous brain deposits, neuroinflammation, cerebrovascular dysfunction, and extensive neuronal loss over time. AD is a multifactorial disease, and lifestyle factors, including diet, are likely associated with the development of AD pathology. Since obesity and diabetes are recognized as risk factors for AD, it might be predicted that a high-fat diet (HFD) would worsen AD pathology. However, modeling HFD-induced obesity in AD animal models has yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Since then, intracerebroventricular injection of STZ has been widely used in animal models to demonstrate impaired neuronal plasticity and learning deficits caused by metabolic diseases [67][68][69]. Moreover, rodent models fed with high-fat diets exhibited all the hallmarks of these degenerative diseases and represented an interesting approach to the study of the phenotypic features and pathogenic mechanisms of NDDs [70,71]. Recently, several genetic models have been suggested with their advantages including capturing both Aβ and phospho-tau as well as maintaining aging features of AD, but high lethality, overexpression of tau protein and limited cognitive impairment were seen in genetic models [72].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, intracerebroventricular injection of STZ has been widely used in animal models to demonstrate impaired neuronal plasticity and learning deficits caused by metabolic diseases [67][68][69]. Moreover, rodent models fed with high-fat diets exhibited all the hallmarks of these degenerative diseases and represented an interesting approach to the study of the phenotypic features and pathogenic mechanisms of NDDs [70,71]. Recently, several genetic models have been suggested with their advantages including capturing both Aβ and phospho-tau as well as maintaining aging features of AD, but high lethality, overexpression of tau protein and limited cognitive impairment were seen in genetic models [72].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our study represents the youngest age at which metabolic, gene expression, and AD‐related alterations related to the interplay between ApoE genotype and diet have been reported for rodents. Our findings are consistent with previous studies in humans (Fitzpatrick et al, 2009; Profenno et al, 2010) and rodent models (Barron et al, 2013; Ho et al, 2004; Moser & Pike, 2017) that examined the role of high‐fat‐induced obesity in increasing risk of AD, as well as with previous studies that found APOE4‐expressing mice to be more susceptible to metabolic disturbances, including visceral adipose tissue accumulation and glucose intolerance compared with APOE3‐expressing mice (Amelianchik et al, 2022; Jones et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…A high‐fat diet (HFD), which is closely correlated with obesity (Freeman & Granholm, 2012; Ho et al, 2004), can interact with ApoE status in a manner that elevates the risk of developing AD (Amelianchik et al, 2022; Johnson et al, 2017; Jones & Rebeck, 2019; Mattar et al, 2022; Sullivan et al, 2011; Zhao et al, 2017). In a human ApoE targeted‐replacement mouse model, HFD alters plasma and hippocampal ApoE levels in an ApoE isoform‐dependent manner, reducing hippocampal ApoE levels in ApoE3 targeted‐replacement mice but not in ApoE4 targeted‐replacement mice (Lane‐Donovan & Herz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Mediterranean‐DASH Diet Intervention for Neurodegenerative Delay diet was shown to slow cognitive decline and, with other healthy lifestyle habits, lengthen the health span of individuals in the study with and without AD 20 . The impact of diet on AD pathogenesis is inconsistent across studies, which may be explained by differences in the start and duration of the treatments and in the composition of the diets 21 . To achieve higher rigor and reproducibility, metabolic dietary effects should be assessed by measuring multiple parameters, such as blood glucose, blood pressure, low‐density and high‐density lipoprotein levels, triglyceride levels, and body weight.…”
Section: Targeting Ad: Going Beyond Amyloid and Taumentioning
confidence: 99%